Protubera beijingensis sp. nov. (Protophallaceae, Phallales) from China - Li, Guojie; Deng, Dejiang; Wei, Jinkang; Zhang, Chulong; Zhao, Ruilin; Lin, Fucheng (Phytotaxa, 2018)
The genus Protubera includes gasteroid species. Its members are globally distributed in tropical, subtropical, and temperate areas, and presently, six species are recognized. In this paper, Protubera beijingensis from North China is described as a new species. Its morphological description and illustration are provided in detail and compared with morphologically similar species. A multigene phylogenetic analysis based on nLSU, atp6, and rpb2 sequences of the genus Protubera also identifies this organism as a new species within Protubera.